Progress in Understanding and Treating SCN2A-Mediated Disorders. Issue 7 (July 2018) - Sanders, Stephan J.; Campbell, Arthur J.; Cottrell, Jeffrey R.; Moller, Rikke S.; Wagner, Florence F.; Auldridge, Angie L.; Bernier, Raphael A.; Catterall, William A.; Chung, Wendy K.; Empfield, James R.; George, Alfred L.; Hipp, Joerg F.; et al.
Abstract : Advances in gene discovery for neurodevelopmental disorders have identified SCN2A dysfunction as a leading cause of infantile seizures, autism spectrum disorder, and intellectual disability. SCN2A encodes the neuronal sodium channel NaV 1.2. Functional assays demonstrate strong correlation between genotype and phenotype. This insight can help guide therapeutic decisions and raises the possibility that ligands that selectively enhance or diminish channel function may improve symptoms. The well-defined function of sodium channels makes SCN2A an important test case for investigating the neurobiology of neurodevelopmental disorders more generally. Here, we discuss the progress made, through the concerted efforts of a diverse group of academic and industry scientists as well as policy advocates, in understanding and treating SCN2A -related disorders. Highlights: Dysfunction in SCN2A has been recently recognized as a major cause of neurodevelopmental disorders (NDDs), including epilepsy, intellectual disability (ID), and autism spectrum disorder (ASD). SCN2A encodes a neuronal sodium channel, NaV 1.2. In contrast to many other NDD-linked genes, there is a well-established body of literature on sodium channel function and dysfunction. Loss of NaV 1.2 function contributes to ASD and ID, whereas gain of function contributes to early onset epilepsy. Such strong and bidirectional genotype–phenotype correlation is rare in brain disorders. Sodium channel function can be enhanced or suppressed using pharmacology. This may allow for future, targeted treatment of SCN2A-associated disorders. The neuropathophysiology revealed by investigating SCN2A may provide insight into the underlying biology of NDDs more generally.